Dialektika hubungan ekonomi Indonesia dan pemberdayaan ekonomi rakyat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRAK This paper deals with the analysis of the position of people's economy in Indonesia. The analysis is based on the dialectics of economic relations in the economy which is the core component of the structuralist approach in economic development. It is found that the interaction among economic actors in Indonesia is exploitative and detrimental to the people's economy. Various national economic policies are also found inducing a negative impact to the position of the people's economy. The presence ofan effective developmental state which is pro-people is the precondition in placing people's economy in the mainstream of the Indonesian economy. The success in uplifting the position of the people's economy is a function of the development of the entire social system. Keywords: economic development,